Sleep Disturbance and Depression in Adults with Steady State Bronchiectasis - Rehman, Iqra; Saeed Zaman, Syed Arif; Ashraf, Junaid; Fayyaz, Maria; Naseem, Sidra; Akram, Fazeelat (Journal of Postgraduate Medical Institute, 2024)
Objective: To study the sleep disturbances and depression in adults with steady-state bronchiectasis. Methodology: This study was conducted at The University of Lahore. This is a descriptive cross-sectional study. Data was collected using Pittsburgh Sleep Quality Index (PSQI) questionnaire for sleep disturbance and Patient Health Questionnaire (PHQ-9) for depression. “Poor sleepers” with a PSQI score of >5, while “good sleepers” with a PSQI score of <5. Steady-state means stable patients of bronchiectasis. Data was entered and analyzed using SPSS 21. Results: A total of 89 patients were included in our study, aged 18 to 80 years, with a mean age of 42.66±17.29 years. There were 53 (59.6%) female patients and 36 (40.4%) male patients. The duration of symptoms ranged from 3 to 6 months. Out of 89 patients, 67.9% suffered from post-TB bronchiectasis, 15.6% suffered from cystic fibrosis, 4.4% of patients suffered from other genetic disorders, 6.67% of patients suffered from Allergic Bronchopulmonary Aspergillosis (ABPA), and 2.2% from post-infectious bronchiectasis. Approximately 1.1% of patients suffered from post-obstructive bronchiectasis. Out of 89 patients with bronchiectasis, 41(46%) were good sleepers, while 48 (53%) were bad sleepers. Out of 89 patients of bronchiectasis, 12(13.5%) had minimal depression, 17(19.1%) had mild depression, 31(34.8%) had moderate depression and 29(32.6%) had moderately-severe depression. Conclusion: The results of this study showed that sleep disturbances and depression were common in patients suffering from bronchiectasis. Patients with moderate to severe bronchiectasis had lower sleep quality and scored low on the PSQI index. Patients with severe disease also scored high on the PHQ-9 index for depression.